Pengaruh Kompetensi terhadap Produktivitas Kerja Karyawan di PT Aroma Wangi Indonesia - Nuniek Dewi Pramanik; Alfazri, Ali (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Examining the relationship between competence and productivity at PT Aroma Wangi Indonesia is the goal of this quantitative research. Thirty workers were selected using a purposive sampling method at random from the respondents inside the organization. We administered tests for normality, linearity, heteroscedasticity, and reliability to our Likert scale surveys, as well as t-tests, reliability analyses, and validity tests, among other statistical procedures, to ensure their data were accurate and reliable. Because the calculated r-value of 9.319 was more than the table r-value of 1.701, with a significance level of 0.000 (< 0.05), the study's findings showed that the independent variable affects the dependent variable. The coefficient of determination test yielded a high R Squared value of 75.6%, lending credence to the hypothesis that competence has a substantial influence on the productivity of PT Aroma Wangi Indonesia personnel. There is a robust relationship between competency and output in the workplace, according to the findings.